PUBLIC AWARENESS OF GLUCOSE-6-PHOSPHATE DEHYDROGENASE(G6PD) DEFICIENCY CAUSES AND PREVALENCE FACTORS - Muath Salman Almuhaini et al (Baqai Journal of Health Sciences)
Glucose 6-phosphate dehydrogenase (G6PD) deficiency is an x-linked disorder that consequently causes the hemolysis of red blood cells (RBCs) when exposed to certain triggering factors like medications, food or disease. The current study aims to determine the awareness and knowledge level of the Saudi community in Riyadh city. A random sample of 86 participants was asked to fill a pre-designed questionnaire examining the awareness and knowledge level about G6PD deficiency. Results of the study indicated that the Saudi community had a poor knowledge level about G6PD deficiency, especially in the pattern of inheritance, symptoms, and factors triggering this disorder. The study also recommends that there is an urgent need to carry out campaigns to increase awareness level in the Saudi community regarding G6PD deficiency